The Essence of the Conceptual Model of Service Enterprises Modernization - Klochko, Elena N.; Nasimov, Dilmurod; Gurfova, Rita V.; Tokareva, Tatyana Y. (International Journal of Economics and Financial Issues, 2016)
The multiplicity of definitions of modernization due to the fact that the very concept of “modernization” has very deep roots, related to the development of human civilization on its inherent social and economic laws. One of the most important laws is the development of the modernization process. Currently, the modernization process scale covers a wide field of human activity that initiates improvement of conceptual provisions of modernization. Modernization theory emerged in the 60s of XX century in the struggle for influence in the Third World. Only by the middle of the 80s, when there was accumulated both positive and crisis experience a large number of Third World countries that have implemented a variety of projects (both in the West and the socialist pattern) formed the theoretical concepts that are suitable to support a relatively non-ideological modernization politician. The result was the understanding of the transformation of the concept of “modernization” in the subject of analysis for representatives of disciplines, from different sides of the practice of “new” countries and analyse the reasons for successes and failures of the relevant development projects. Keywords: enterprise economy, service, modernization of enterprises, management model JEL Classifications: D22, D24, L26, L82